2017
DOI: 10.1038/npp.2017.169
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide S Induces Acute Anxiolysis by Phospholipase C-Dependent Signaling within the Medial Amygdala

Abstract: Neuropeptide S (NPS) is an important anxiolytic substance of the brain. However, the signaling pathways downstream of NPS receptor (NPSR) activation, underlying the behavioral effect of NPS, remain largely unknown. Here, we show that bilateral microinfusion of NPS (0.2 nmol/0.5 μl) into the medial amygdala (MeA) of male adult Wistar rats reduced anxiety-related behavior on both the elevated plus-maze and the open field. Moreover, as shown in amygdala tissue micropunches intracerebroventricular infusion of NPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…The NPS effects on intracellular Ca 2ϩ also studied in NPSR1-transfected HEK293T and CHO cells are most likely mediated by NPSR-induced G q signaling (Reinscheid et al, 2005;Liao et al, 2016;Clark et al, 2017). In vivo, it has recently been demonstrated that NPS promotes anxiolysis in a phospholipase C-dependent manner and increases intracellular Ca 2ϩ levels characterized by increased phosphorylation and synthesis of Ca 2ϩ /calmodulin-dependent kinase II within the rat medial amygdala (Grund and Neumann, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The NPS effects on intracellular Ca 2ϩ also studied in NPSR1-transfected HEK293T and CHO cells are most likely mediated by NPSR-induced G q signaling (Reinscheid et al, 2005;Liao et al, 2016;Clark et al, 2017). In vivo, it has recently been demonstrated that NPS promotes anxiolysis in a phospholipase C-dependent manner and increases intracellular Ca 2ϩ levels characterized by increased phosphorylation and synthesis of Ca 2ϩ /calmodulin-dependent kinase II within the rat medial amygdala (Grund and Neumann, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the complexity of NPSR signaling has been recently underlined by the identification of NPSR biased agonists, such as NPS (1‐10) and SFKN‐NH 2, that preferentially signal through IP 3 ‐DAG‐Ca 2+ second messengers. This class of NPSR ligands may be useful as innovative anxiolytics . Despite this NPSR signaling complexity, structure‐activity relationship studies and drug discovery programs targeting NPSR have been conducted so far only with classical single end‐point assays (for reviews see and ).…”
Section: Discussionmentioning
confidence: 99%
“…This class of NPSR ligands may be useful as innovative anxiolytics. 36,37 Despite this NPSR signaling complexity, structure-activity relationship studies and drug discovery programs targeting NPSR have been conducted so far only with classical single end-point assays (for reviews see 4 and 5). This approach may be reductionist and incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…The hyperlocomotor effects of NPS are robust and have been replicated by several laboratories around the world ( Table 1 ). The pioneer study of Xu and collaborators [ 2 ] showed that central administration of NPS increases locomotor activity in mice at lower doses (0.1 nmol), and this effect lasts for about 1 h. These findings were largely replicated [ 4 , 19 , 20 , 26 , 27 , 67 ] and extended to rats [ 33 , 34 , 35 , 36 ]. Distinct from classical psychostimulant drugs (i.e., amphetamines), repeated NPS injections did not lead to locomotor sensitization [ 34 ].…”
Section: Behavioral Effects Of Neuropeptide S: Implications For Parkinson Diseasementioning
confidence: 99%